ETHICS AND THE COMPLEXITY OF TECHNOLOGY: A DESIGN APPROACH - de Vries, Marc J. (Philosophia reformata, 2006)
In this article I will show how the conceptual framework for analyzing reality as developed in reformational philosophy can help us to get a fuller understanding of the ethics of technology than in popular reductionist views. Thereby I will use Caroline Whitbeck’s suggestion that ethical problems should be dealt with as if they were design problems. Reformational philosophy helps us to understand the nature of complexity in design and also how order in this complex chaos can be created by observing the various functions of technical artifacts. In line with the current empirical turn in the philosophy of technology, I will illustrate this by describing a case study: nanotechnology.